2019
DOI: 10.1016/j.neuron.2019.07.028
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Circuit Arbitrates between Persistence and Withdrawal in Hungry Drosophila

Abstract: SummaryIn pursuit of food, hungry animals mobilize significant energy resources and overcome exhaustion and fear. How need and motivation control the decision to continue or change behavior is not understood. Using a single fly treadmill, we show that hungry flies persistently track a food odor and increase their effort over repeated trials in the absence of reward suggesting that need dominates negative experience. We further show that odor tracking is regulated by two mushroom body output neurons (MBONs) con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 80 publications
(144 reference statements)
8
116
0
Order By: Relevance
“…Neuronal reconstruction for this project took place in a collaborative CATMAID environment, in which in which 27 labs are participating to build draft connectomes for specific circuits. As a consequence, work done for other published (Dolan et al [13,15], Zheng et al [21], and Sayin et al [72]) and ongoing projects has also proved useful to us. We thank Fiona Love, Billy Morris, Amelia Edmondson-Stait, Laia Ser- Theiss for together contributing~30% of the novel neuronal cable used in this study manuscript.…”
Section: Acknowledgementsmentioning
confidence: 86%
“…Neuronal reconstruction for this project took place in a collaborative CATMAID environment, in which in which 27 labs are participating to build draft connectomes for specific circuits. As a consequence, work done for other published (Dolan et al [13,15], Zheng et al [21], and Sayin et al [72]) and ongoing projects has also proved useful to us. We thank Fiona Love, Billy Morris, Amelia Edmondson-Stait, Laia Ser- Theiss for together contributing~30% of the novel neuronal cable used in this study manuscript.…”
Section: Acknowledgementsmentioning
confidence: 86%
“…6A) that has a long vertical medial projection (see also (Wu et al, 2019). We manually detected all synaptic connections, as done previously Sayin et al, 2019;Zheng et al, 2018). After excluding very weak connections (using 3 synapses as a threshold, see Methods), we counted 417 presynaptic and 421 postsynaptic sites ( Fig.…”
Section: Pc1-alpha Is Reciprocally Connected To a Specific Subset Ofmentioning
confidence: 99%
“…Internal brain states influence perceptions, decision-making, and actions (Anderson, 2016;Berridge, 2004;Lorenz and Leyhausen, 1973) -for example, when hungry, we make different decisions about what to do (prioritizing searching out food over other tasks) and what to eat (expanding the repertoire of foods we find appetizing) based on our hunger status (Sayin et al, 2019;Sternson et al, 2013). The timescales of persistence of an internal brain state can varysome, like sleep-wake cycles, persist over hours (Scammell et al, 2017;Shaw et al, 2000), while others may last only a few seconds (Calhoun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Does this range encompass functional connections? While there is no single answer for how many synapses constitute a ‘functional connection’, recent work has found that seemingly low connection strengths, in the region of rv2% of a neuron’s total post-synaptic budget, can be functional [12, 16, 38, 48]. In the case of PD2a1/b1 and AV1a1neurons used in this study, the average number of post-synapses per neuron is 673, implying a 2% threshold value of around 12 synapses (Table S16).…”
Section: Discussionmentioning
confidence: 99%